CD169+ Macrophages Capture and Dendritic Cells Instruct: The Interplay of the Gatekeeper and the General of the Immune System - Grabowska, Joanna; Lopez-Venegas, Miguel A.; Affandi, Alsya J.; den Haan, Joke M. M. (Frontiers in Immunology, 2018)
Since the seminal discovery of dendritic cells (DCs) by Steinman in 1973, there has been an ongoing debate to what extent macrophages and DCs are related and perform different functions. The current view is that macrophages and DCs originate from different lineages and that only DCs have the capacity to initiate adaptive immunity. Nevertheless, as we will discuss in this review, lymphoid tissue resident CD169+ macrophages have been shown to act in concert with DCs to promote or suppress adaptive immune responses for pathogens and self-antigens, respectively. Accordingly, we propose a functional alliance between CD169+ macrophages and DCs in which a division of tasks is established. CD169+ macrophages are responsible for the capture of pathogens and are frequently the first cell type infected and thereby provide a confined source of antigen. Subsequently, cross-presenting DCs interact with these antigen-containing CD169+ macrophages, pick up antigen and activate T cells. The cross-priming of T cells by DCs is enhanced by the localized production of type I interferons (IFN-I) derived from CD169+ macrophages and plasmacytoid DCs (pDCs) that induces DC maturation. The interaction between CD169+ macrophages and DCs appears not only to be essential for immune responses against pathogens, but also plays a role in the induction of self-tolerance and immune responses against cancer. In this review we will discuss the studies that demonstrate the collaboration between CD169+ macrophages and DCs in adaptive immunity.